Quantitative Observations On The Pulmonary Anatomy Of The Domestic Fowl And Other Ground-Dwelling Birds - M. K. Vidyadaran, . (1987)
The pulmonary stereology of the adult domestic fowl (Gallus gallus variant domesticus) , the Red Jungle Fowl (Gallus gallus) , the Muscovy Duck (Cairina moschata) , the White-breasted Water-Hen (Amaurornis phoenicurus), and the juveniles of the domestic fowl and Red Jungle Fowl were investigated. The lung of the domestic fowl was canpared with that of the Red Jungle Fowl at day 1 , day 7, and day 30 . A multistage sampling technique was used for pulmonary stereology. Standard stereological procedures of point counting, intersection counting, and measurement of intercept length, were employed for estimating volume density, surface area, and harmonic mean thickness respectively. The anatomical diffusing capacity was estimated from Weibel's model. The pulmonary stereological characteristics of the Red Jungle Fowl are broadly similar to those of the domestic fowl, but the Red Jungle Fowl has a higher specific volume of the lung and a thinner blood-gas (tissue) barrier, with a higher specific diffusing capacity of the barrier for oxygen than the domestic fowl. The lung of the White-breasted Water-Hen, a grounddwelling bird, has stereological characteristics similar to sane flying birds (non-passerine), thus showing that not all ground-dwelling birds have inferior pulmonary stereological characteristics. The domestic Muscovy Duck has pulmonary characteristics which are broadly similar to those reported for other Anseriformes, except for a greater thickness of the blood-gas (tissue) barrier. The specific oxygen diffusing capacity of the blood-gas (tissue) barrier was well below that of other anseriforms and birds in general. The juvenile of both the domestic fowl and the Red Jungle fowl has a thicker blood-gas (tissue) barrier than the adult. In each age group examined, the blood-gas (tissue) barrier was thicker in the domestic fowl than in the Red Jungle Fowl.